Management of grade IV blunt renal trauma in adults: Systematic review and meta-analysis - Bramono, Ikhlas A; Irdam, Gampo A; Rodjani, Arry; Wahyudi, Irfan (UI Scholars Hub, 2019)
Background: Irrespective of the high incidence of grade IV renal trauma, there is still an ongoing debate regarding the use of conservative and surgical approaches for its treatment. This study aimed to conduct pooled analyses of published studies that concluded evidences regarding the management of grade IV renal trauma. Methods: Published studies between 1995 and 2015 from Cochrane Library, EBSCO, Embase, ProQuest, PubMed, and Scopus were reviewed and pooled analysis of eligible studies was conducted using random effects model. Heterogeneity was presented with I2 and p value. Results: Eleven studies reporting on 703 adults were included in the analysis. Conservative approach was used in 611 patients (conservative group) and surgical approach in 92 patients (surgical group); success rate and morbidity were comparable between the groups (risk ratio (RR): 1.15, 95% confidence interval (CI): 0.72–1.83; RR: 0.77, 95% CI: 0.27–2.21, respectively). The trend of mortality was higher in the surgical group than the conservative group. Conclusions: A comparable success rate was observed between the groups. Mortality was higher in the surgical group than the conservative group. As advocated by many guidelines, conservative management may decrease unnecessary exploration, which can ultimately reduce reconstruction and/or nephrectomy rate without causing morbidity or mortality.